2011
DOI: 10.1111/j.1460-2695.2011.01606.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of several TIG weld repairs on the axial fatigue strength of AISI 4130 aeronautical steel‐welded joints

Abstract: A B S T R A C T Welded joints of airframes critical to the flight-safety are commonly repair welded during its operational live. In this study, the effect of up to three weld repairs by gas tungsten arc welding (GTAW) on the axial fatigue strength of AISI4130 steel used in an airframe critical to the flight-safety was investigated. The tests were performed on hot-rolled steel plate specimens, 0.89 mm thick, with load ratio R = 0.1, constant amplitude, at 20 Hz frequency and room temperature. The results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The nonmetallic inclusions inside the steel material are pressed into flakes after rolling, which causes the thick plates become layered and the mechanical properties through-thickness becomes worse. 5,6 Additionally, the huge amount of the welding heat input will induce the steel material adjacent welds become worse and the toughness decrease, 7 and the crack is liable to occur during the cooling process after welding. 2 Furthermore, as the plate thickness increases, the stress along depth in the defect increases, and the defect will be subjected to triaxial tension.…”
Section: N O M E N C L a T U R Ementioning
confidence: 99%
“…The nonmetallic inclusions inside the steel material are pressed into flakes after rolling, which causes the thick plates become layered and the mechanical properties through-thickness becomes worse. 5,6 Additionally, the huge amount of the welding heat input will induce the steel material adjacent welds become worse and the toughness decrease, 7 and the crack is liable to occur during the cooling process after welding. 2 Furthermore, as the plate thickness increases, the stress along depth in the defect increases, and the defect will be subjected to triaxial tension.…”
Section: N O M E N C L a T U R Ementioning
confidence: 99%
“…Although the Mk factors at the deepest points from Lie et al underestimate the Mk-a/t curves, both values have much in common from the aspect of the tendency and behaviour of the Mk-a/t curve. Judging by these similarities, the Mk factor solutions for the three welded joints permit its use in calculating the stress intensity factors for multiple surface cracks as shown in Eqs (1) and (2).…”
Section: Mk Factor Solutionsmentioning
confidence: 99%
“…The mechanisms associated with the propagation of these cracks involve the mutual interactions and coalescence of two adjacent cracks. When the cracks extend through the thickness of their members, the structural strength of the components subsequently decreases rapidly . An assessment of the fracture mechanics of these weld toe cracks requires accurate the stress intensity factor solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an investigation on 157 engine-cradle failure reports of Brazilian T-25 Universal aircrafts indicated that all failures occurred at welded joints as a result of fatigue cracks. As a consequence of these successive repair welding operations, the interval between inspections ("Time-Before-Fail") was reduced from 4000 h to 50 h of flight (Nascimento, 2004). Motivated by the high failure incidence on this component, an extensive research program to evaluate the effects of the repair welding on its structural integrity, mechanical properties and microstructure has been developed.…”
Section: Introductionmentioning
confidence: 99%